Images that we should not see. The issue of non-perceptual attitudes from film to virtual reality (AN-ICON. Studies in Environmental Images [ISSN 2785-7433], 2022)
This paper casts film experience as a sort of disembodied perception. I will show how this experience can be manipulated and altered in order to approximate to mental states of fictional characters, in particular embodied perception, memory and imagination. I will acknowledge that film experience can approximate to non-perceptual attitudes such as memory and imagination much better than the experience elicited by theater. Yet, I will contend, film experience cannot emulate the phenomenology of non-perceptual attitudes since it remains a sort of disembodied perception even when it is manipulated by filmmakers in order to approximate memory states or imaginative states of fictional characters. Finally, I will argue that virtual reality, in virtue of both its proximity to embodied perception and its potential for manipulation, is, in principle, in a better position than film when it comes to trying to emulate non-perceptual attitudes such as memory and imagination.
Keywords: Film; Virtual Reality; Perception; Memory; Imagination